Merdeka Belajar: Solusi Awal Transformasi Pendidikan Indonesia? - Vira Rizki Amalia; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2023)
The purpose of this study is to find out the independent learning method that can be implemented in schools and to find out the assessment system in the Merdeka Belajar program as a school graduation requirement. This study report uses a descriptive qualitative method by taking notes because the source of the data was obtained by listening to an oral narrative from the CNN Indonesia Youtube channel entitled